1998
DOI: 10.1046/j.1365-2168.1998.00530.x
|View full text |Cite
|
Sign up to set email alerts
|

Radical and nerve-preserving surgery for rectal cancer in the Netherlands: a prospective study on morbidity and functional outcome

Abstract: A relationship between sacrifice of specific nerve structures and accompanying dysfunction was established. The nerve-preserving technique yields good results in terms of morbidity and functional outcome, and should be considered for adoption as a standard surgical procedure for primary rectal cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
110
1
7

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 176 publications
(125 citation statements)
references
References 23 publications
7
110
1
7
Order By: Relevance
“…Using IPSS, resultant bladder dysfunction was 90% and 3 months post-surgery 33 patients were having same IPSS as before surgery, so at 3 months after surgery resultant bladder dysfunction was 28%. This is consistent with results with other studies i.e., Kim et al [12], Maas et al [22] and Ameda et al [23], as the voiding dysfunction in their studies were 26%, 28% and 30% respectively.…”
Section: Bladder Functionsupporting
confidence: 83%
See 2 more Smart Citations
“…Using IPSS, resultant bladder dysfunction was 90% and 3 months post-surgery 33 patients were having same IPSS as before surgery, so at 3 months after surgery resultant bladder dysfunction was 28%. This is consistent with results with other studies i.e., Kim et al [12], Maas et al [22] and Ameda et al [23], as the voiding dysfunction in their studies were 26%, 28% and 30% respectively.…”
Section: Bladder Functionsupporting
confidence: 83%
“…During rectal surgery, the ANP procedure causes less impairment of genitourinary function [22,28,31]. Similarly, our study showed no significant complications related to voiding.…”
Section: Sexual Functionsupporting
confidence: 46%
See 1 more Smart Citation
“…After unilateral resection the majority of patients can urinate spontaneously again only after 2 months. (59,99). Vesicourethral dysfunction occurs after LAR and APE in the early post-operative phase in 30 -70 % of patients if the autonomic nerves are not specifically preserved or cannot be correctly identified in an effort to preserve the nerves (1,76,77) Obstructive disorders after surgery attract more attention as they have to be treated acutely, although continence disorders are also common.…”
Section: Voiding Disorders After Larmentioning
confidence: 99%
“…The connection between preservation of the nerves and preservation of bladder function could be demonstrated by intra-operative neuromonitoring (77).In patients with an positive test regarding an adequate increase in bladder pressure,the IPPS items weak stream,incomplete emptying and frequency of micturition varied significantly from those with negative test result. According to various studies, if the autonomic nerves are identified the VD rate can be expected to fall significantly to between 0 and 23 %, whereby generally rates of about 10 % and lower are given and some of the patients had a pre-existing VD (2,6, 35,46,70,75,77,99,114,133). Risk factors for VD are pre-existing disorders, tumor size over 5 cm (75), deep-seated tumor and APE (155,157), blood loss (84), age > 65 years (155).…”
Section: Voiding Dysfunction (Vd) In Preserving Autonomic Nerve Procementioning
confidence: 99%